Implementing Professional Standard for Teachers: The Need for the Next Step - Yamburg Ye.S (Moscow State University of Psychology and Education, 2016)
The paper analyses the first stage of the implementation of the professional standard for teachers. This stage involved the approbation of the standard on regional testing grounds. As a result, most teachers became psychologically ready for the implementation of the standard and aware of the new professional competencies that they would have to acquire. At the same time, this stage helped to reveal the reasons of low efficiency in the acquisition of the standard, its problems and contradictions. This paper focuses on the ways of overcoming the revealed difficulties. Basically it means improving the management model of implementing the professional standard. This model, in turn, must include a conceptual basis and legal support of the implementation. The author argues that the key factor promoting the efficiency of the implementation of the professional standard for teachers is the realization of the principle of state and public management, which is especially important in the case of work and qualification assessment. It is necessary to think over and ensure (on the legal level as well) that experts from the professional community take part in assessment procedures. This would help to raise the teachers' trust in changes within the educational system.